Collaborations at the level of Romanian academic libraries - Madge, Octavia Luciana (Qualitative and Quantitative Methods in Libraries; Vol 2 No 3 (2013): September 2013 Issue, 2017)
During the last two decades specialists underlined many times the need for a co-operation policy at the level of Romanian academic libraries. At the same time, the lack of co-operation and the inhability of reaching a common direction have been pointed out and criticized. Despite the fact that Romanian libraries and librarians are not the best example in this area examples of collaborations between these libraries can be found during the past years. In order to investigate the different reasons for this lack of cooperation we decided to conduct a research at the level of academic libraries in this country. Part of this research consists in an analysis of the way in which collaborations in the space of Romanian academic libraries are reflected in some of the main LIS (Library and Information Science) Romanian journals. Another important part consists of a questionnaire survey at the level of academic libraries’ directors. The paper presents some preliminary results of this research and comes with examples from one branch of a large academic library in Romania which refer only to collaborations with the academic staff, students, and the faculty, and which involve different kinds of resources available in the library.